Flight from law: a competing risks model of departures from law firms. - Kay, Fiona M. (Law & Society Review, 1997)
Temporal dimensions of career mobility within the legal profession for a sample of Canadian lawyers are examined. Using a continuous-time stochastic model of the underlying process of movement across work settings, factors explaining gender variances in career paths are analyzed. Findings imply that women's integration into the legal profession is still marginal: Women are still underrepresented in law firm partnerships, moving significantly slower than men toward such positions. Furthermore, women exit law firm practice at a significantly higher rate than do their male counterparts. The empirical data implies that the quickly growing size of entry cohorts has limited the number of partnerships available to aspiring associates and has hastened lawyers' exit from law firm practice. Emerging paths from law are recorded, and causal factors driving lawyers out of firm practice and those luring them toward other more attractive options are examined.